The impact of a breast cancer diagnosis on marital outcomes and factors associated with divorce and separation - Gustavo Werutsky; Mahira Lopes; Rafaela Gomes de Jesus; Antonia Angeli Gazola; Rodrigo Azevedo Pellegrini; Taiane Francieli Rebelatto; Laura von Wallwitz Freitas; Ana Paula Heck; Arthur Ferreira da Silva; Matheus Füehr Rodrigues; Gustavo Gössling; Juliana Giacomazzi; et al. (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective To analyze marital outcomes, divorce or separation, and its association with demographic, socioeconomic, and clinicopathological factors among breast cancer (BC) survivors after 2-years of diagnosis. Methods We performed a retrospective analysis of marital status at baseline and at years 1 and 2 of follow-up of women aged ≥ 18 years diagnosed with invasive BC participating in the AMAZONA III (GBECAM0115) study. The BC diagnosis occurred between January 2016 and March 2018 at 23 institutions in Brazil. Results Of the 2974 women enrolled in AMAZONA III, 599 were married or living under common law at baseline. Divorce or separation occurred in 35 (5.8%) patients at 2 years of follow-up. In the multivariate analysis, public health insurance coverage was associated with a higher risk of marital status change (8.25% vs. 2.79%, RR 3.09, 95% CI 1.39 - 7.03, p = 0.007). Women who underwent mastectomy, adenomastectomy or skin-sparing mastectomy were associated with a higher risk of divorce or separation (8.1% vs. 4.49%, RR 1.97, 95 CI 1.04 - 3.72, p = 0.0366) than those who underwent breast-conserving surgery. Conclusion Women covered by the public health system and those who underwent mastectomy, adenomastectomy or skin-sparing mastectomy were associated with a higher risk of divorce or separation. This evidence further supports the idea that long-term marital stability is associated with a complex interplay between socioeconomic conditions and stressors, such as BC diagnosis and treatment. ClinicalTrials Registration: NCT02663973.